Implementasi Pembelajaran Pendidikan Pancasila Dalam Kurikulum Merdeka Di SMP Kertanegara Malang - Rivaldo Rius Siafu; Romadhon Romadhon; Didik Iswahyudi (International Forum of Researchers and Lecturers, 2023)
The implementation of pancasila education learning in the independent curriculum is very important for teachers and students, because it has pancasila values and must be instilled in teachers and students. The importance of this research is that there are important things that must be considered in this research, namely in order to achieve the expected educational goals, quality and effective learning is needed. So what must be pursued by educators is to use the curriculum which is a key in the implementation of education. The purpose of this study is to find out school policies related to the implementation of pancasila education learning in the independent curriculum at SMP Kertanegara Malang, find out how the implementation of pancasila education learning in SMP Kertanegara Malang. and teachers in the implementation of pancasila education learning at SMP Kertanegara Malang. This research method uses qualitative, descriptive. With finished data What is used is observation, interviews and documentation, data analysis techniques use triangulation to obtain the validity of the data. Data analysis used in the study is Reduction, Display and Verification. Based on the results of this study, it shows that: (1) teachers in pancasila education subjects at SMP Kertanegara Malang have implemented an independent curriculum in the 2022/2023 school year. (2) Learning resources are not only limited to guidelines determined by the center, but learning resources can be obtained from anywhere, as long as their nature is positive and supports the cognitive realm of students. Based on the conclusion that the implementation of pancasila education learning in the independent curriculum at SMP Kertanegara Malang, is marked by the implementation of a learning process in which teachers become facilitators and mediators as well as motivators for students so that they are enthusiastic about learning in the independent curriculum.